Pencetakan Mushaf Al-Qur’an di Indonesia - Akbar, Ali (SUHUF, 2011)
This article outlines the development of the printing of the Qur’an in Indonesia from its advent in the middle of 19th century to the present. It also traces the influence of printed Qur’ans from India and Turkey on the early period of Qur’anic printing in Indonesia, and gives brief descriptions of some publishers of the Qur’an throughout the period in question. The last section analyses recent creative developments in the Qur’an publishing industry in Indonesia.